Integrated metabolite profiling and transcriptome analysis unraveling mechanism of RC catabolism in Paenarthrobacter ilicis CR5301 - Li, Hongfei; Sun, Daqing; Cao, Longkui; Wang, Baohui (Frontiers in Microbiology, 2023)
Steviol glycosides are ideal sweeteners, widely used in food, medicine, and cosmetics. Rebaudioside C (RC) is considered to be the most third abundant steviol glycoside, which has a bitter aftertaste to limit its application. Hydrolysis of RC to generate other bioactive steviol glycosides is an effective way to promote its additional utilization. In our previous study, a bacterium Paenarthrobacter ilicis CR5301 for hydrolyzing RC with high efficiency was isolated and identified. Herein, the expression profiles of P. ilicis CR5301 in the deletion and presence of RC were investigated by RNA-Seq. The RC metabolites were identified by High Performance Liquid Chromatography and Ultra Performance Liquid Chromatography-Triple-Time of Flight Mass Spectrometer. Four aspects of research gained novel results. Firstly, the identification of metabolites revealed that four metabolites, dulcoside A, dulcoside B, dulcoside A1, and steviol were produced during RC metabolism. Secondly, RNA-Seq analyses unraveled that 105 genes of P. ilicis CR5301 were significantly differentially expressed, and 7 pathways were significantly enriched. Thirdly, the independent RT-qPCR verified the accuracy and reliability of RNA-seq results. Finally, a complete catabolic model of RC in P. ilicis CR5301 was proposed, and key genes were indicated in RC catabolic metabolism by combining with literature and sequence alignments. This work has comprehensively and clearly unraveled the genes and pathways of RC catabolism in P. ilicis CR5301 at the transcriptional and metabolic levels. It provided new insights and evidence for understanding the mechanism of RC catabolism in bacteria. Key candidate genes will potentially be contributed to the RC hydrolysis and preparation of other functional steviol glycosides in the future.